Screening for ephedrine in some herbal food supplements using thin layer chromatography - Pagsanhan, Evangeline P.; Goyena, Ma. Fe C.
Some herbal food supplements have been reported to have "energized" its users, the same way as alkaloids like ephedrine, a sympathomimetic agent, exerts its physiological effects. Twenty eight (28) herbal food supplements were analyzed for the presence of ephedrine using a two-step method, the general color reaction test for alkaloids and thin layer chromatography. Three (3) samples, representing 10.7 % of the total number of samples analyzed, were found positive for ephedrine. This result is significant because ephedrine is a regulated substance which should not be present in any form unless it is declared in the label and approved by the regulating authority.(Author)
BFAD Laboratory Information Bulletin, 1997 3 (1) pages 8-11
Keywords: Ephedrine; Dietary Supplements -- analysis